Gasification of empty fruit bunch briquette in a fixed bed tubular reactor for hydrogen production - Nyakuma, Bemgba Bevan (2013)
The gasification of EFB briquette was investigated in a fixed bed tubular reactor to examine the effects of temperature on gas composition, heating value and cold conversion efficiency.The resultsrevealedthat H2 gas composition increased from 17.17 mol. % to 29.67 mol. % with increasing temperature from 600°C to 700°C at an equivalence ratio (ER) of 0.4. The heating value (HHV) of the producer gas increased from 6.18 MJ/Nm3 to 7.64 MJ/Nm3 and cold gas efficiency increased from 35.19% to 43.50% with increasing temperature during gasification. However, carbon conversion efficiency increased only marginally from 31.85% to 32.84% while a significant quantity of char (~ 21%) was produced per unit mass of EFB briquette. The results indicate that higher temperatures are required to increase the overall efficiency of EFB briquette gasification in a fixed bed tubular reactor.